Recent advances in the treatment of Duchenne muscular dystrophy. Issue 9 (September 2021) - Willis, Tracey
Abstract: Duchenne muscular dystrophy (DMD) is an x-linked, progressive, incurable disease which affects approximately 1 in 3, 500–5, 000 live boy births. The condition is caused by a lack of a functional protein, dystrophin, in the muscle. Exciting new advances have been made in the treatment of this condition, including genetic treatments. Treatments for DMD have improved over the last 5–10 years, both a combination of improved standards of care and equity across treating centres as well as access to clinical trials and some treatments that have been approved as a result of clinical trials. This review will cover both the updated standards of care and recommended treatments as well as the newer drugs and trials including genetic modification therapies, gene therapy, small molecules to increase the levels of dystrophin related protein and mutation non-specific anti-inflammatory and anti-fibrotic approaches.